Paraboliczny wymiar prologu do Sędziwoja Józefa Bohdana Dziekońskiego. - Naplocha, Anna (Bialostockie Studia Literaturoznawcze, 2017)
The article interprets the metaphor of Phoenix in Józef Bohdan Dziekoński's novel Sędziwoj. The symbolism of the mythical figure offers a structural frame which unites the whole novel. This motif, which appears in the opening and closing part of the text, is a parabolic representation of the characters' fortunes and constitutes quasi-biographies of Kosmopolita and Sędziwoj. Also the very introduction, which is based on the Herder's legend, outlines the entire novel. Finally, drawing from cultural studies, the article frequently refers to symbolism and alchemy.